Decolonizing and Africanising the Curriculum: The How’s Through Reflexivity at a Rural South African University - Tshuma, Tholani (Universitas Negeri Semarang, 2025)
This research sought to examine the academic perceptions and practices that could enhance the decolonisation and Africanisation of the curriculum at a rural South African university. The reflective object inquiry which involved the researcher and seven other academics from different disciplines was followed in a bid to answer one main research question: How could one decolonize and Africanise the curriculum at a rural institution of higher learning? The researcher engaged in reflexivity with the aid of an artefact for photo-elicitation on the idea/concept of decolonisation and Africanisation of the curriculum in higher education. The reflective object inquiry process involved the researcher and seven multidisciplinary academics. The visual aspect of the selected objects triggered reflexivity through the photo-elicitation of rooted views and perspective about decolonization and Africanisation of the content for teaching. The critical feedback from the seven other academics on the held ideas informed the planning and teaching in ways that attempted to decolonise and Africanise the curriculum when teaching the topic of biological fermentation. The seven academics, in their validation role through continuous feedback, observed how the researcher enacted the decolonisation and Africanisation of the curriculum during lecturing. The collected data included the discussion scripts with the academics, lecture observation reports, and journal entries by the researcher. Data was analysed thematically through the process of coding from a deductive to an inductive approach. It emerged that contextualising the content for teaching through integrating it with the students’ everyday lives, IKS and indigenous games is synonymous with simplification of the content for teaching, using humanising pedagogies and decolonising and Africanising the curriculum. These pedagogical practices which involve thinking out the box, beyond the textbooks and educators getting out of their comfort zones in terms of their content preparation, representation and presentation is one way of taking off the burden to explain abstract concepts and potentially maximise student learning.